(untitled) (CIPEEX, 2025)
This scientific article aims to analyze the problem of wildfires in Brazil in 2024 from the perspective of environmental law, investigating the existing legal framework and governmental actions implemented to address this serious environmental issue. The research covers relevant legislation, quantitative aspects of wildfires (with the caveat of the availability of consolidated data), the performance of the federal government and the judiciary, as well as proposals for sustainable development as a way to mitigate negative impacts. The analysis seeks to identify weaknesses and advances in environmental protection, contributing to the debate on the need for more effective measures for the prevention and control of forest fires in the country.